Gratitude at Work: Prospective Cohort Study of a Web-Based, Single-Exposure Well-Being Intervention for Health Care Workers - Adair, Kathryn C; Rodriguez-Homs, Larissa G; Masoud, Sabran; Mosca, Paul J; Sexton, J Bryan (JMIR Publications, 2020)
BackgroundEmotional exhaustion (EE) in health care workers is common and consequentially linked to lower quality of care. Effective interventions to address EE are urgently needed. ObjectiveThis randomized single-exposure trial examined the efficacy of a gratitude letter-writing intervention for improving health care workers' well-being. MethodsA total of 1575 health care workers were randomly assigned to one of two gratitude letter-writing prompts (self- vs other focused) to assess differential efficacy. Assessments of EE, subjective happiness, work-life balance, and tool engagement were collected at baseline and 1-week post intervention. Participants received their EE score at baseline and quartile benchmarking scores. Paired-samples t tests, independent t tests, and correlations explored the efficacy of the intervention. Linguistic Inquiry and Word Count software assessed the linguistic content of the gratitude letters and associations with well-being. ResultsParticipants in both conditions showed significant improvements in EE, happiness, and work-life balance between the intervention and 1-week follow-up (P<.001). The self-focused (vs other) instruction conditions did not differentially predict improvement in any of the measures (P=.91). Tool engagement was high, and participants reporting higher motivation to improve their EE had higher EE at baseline (P<.001) and were more likely to improve EE a week later (P=.03). Linguistic analyses revealed that participants high on EE at baseline used more negative emotion words in their letters (P=.005). Reduction in EE at the 1-week follow-up was predicted at the level of a trend by using fewer first-person (P=.06) and positive emotion words (P=.09). No baseline differences were found between those who completed the follow-up assessment and those who did not (Ps>.05). ConclusionsThis single-exposure gratitude letter-writing intervention appears to be a promising low-cost, brief, and meaningful tool to improve the well-being of health care workers.